2012
DOI: 10.1016/j.physletb.2011.12.062
|View full text |Cite
|
Sign up to set email alerts
|

Unruh gamma radiation at RHIC?

Abstract: Varying the proposition that acceleration itself would simulate a thermal environment, we investigate the semiclassical photon radiation as a possible telemetric thermometer of accelerated charges. Based on the classical Jackson formula we obtain the equivalent photon intensity spectrum stemming from a constantly accelerated charge and demonstrate its resemblances to a thermal distribution for high transverse momenta. The inverse transverse slope differs from the famous Unruh temperature: it is larger by a fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…To extract the spectrum of the photons radiated from the classical electromagnetic fields, Ref. [20] employs an interpretation that the frequency distribution of the radiation energy as the energy distribution of photons with the help of Einstein's relation. On the other hand, it is known that the classical electromagnetic field can be interpreted as the wave function of the corresponding photons [23][24][25][26].…”
Section: Wigner Function Of Electromagnetic Fieldsmentioning
confidence: 99%
“…To extract the spectrum of the photons radiated from the classical electromagnetic fields, Ref. [20] employs an interpretation that the frequency distribution of the radiation energy as the energy distribution of photons with the help of Einstein's relation. On the other hand, it is known that the classical electromagnetic field can be interpreted as the wave function of the corresponding photons [23][24][25][26].…”
Section: Wigner Function Of Electromagnetic Fieldsmentioning
confidence: 99%
“…One can reinterpret this phenomenon a e-mail: horvath.miklos@wigner.mta.hu quasi-classically as the emission of photons. It is straightforward to calculate the differential yield of emitted photons when the charge accelerates uniformly on a straight line [17],…”
Section: Radiation Produced By Decelerating Sourcesmentioning
confidence: 99%
“…Or we experience pseudo-thermalization and pseudo-flow? Some hints towards that this might be the case dates back to 1975, when it was shown that simple acceleration may produce a thermal feeling, it may lead to radiation spectra appearing as the black-body radiation [2,3,4,5].…”
Section: Thermalizationmentioning
confidence: 99%